Measuring the Content of 16 PAH in Plant (potato) from Bradford in the UK - Hamed, Heiam (Scientific Journal for Faculty of Science-Sirte University, 2022)
The objective of this study was to determine the spatial distribution of the PAH (polycyclic aromatic hydrocarbons) concentrations in a sample of potatoes from Bradford, this objective will be achieved by solvent extraction and analysis of potato samples using gas chromatography with mass spectrometry (GC-MS). The potato samples were collected from four sites in the city of the Bradford-middle north of the United Kingdom. The exact location of each sample was recorded using a Global Positioning System (GPS). In site 1 the average concentration of Benzo[b]fluoranthene was (9.82 ng/g). This compound had the highest concentrations level of the 16 PAHs in all sites, while the average (1.023 ng/g) in site 2 of the compound with the low-value Pyrene. The total concentration of 16 PAHs range was between 50.87 -78.31 ng/g.